2009
DOI: 10.4149/neo_2009_01_84
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical therapy of plasma cell neoplasia of the spine

Abstract: Presented is a retrospective analysis of 27 patients with plasma cell neoplasms of the spine treated by surgery. Multiple myeloma was confirmed in 22 (81%) and solitary plasmacytoma in 5 patients (19%), assessed at the time of surgery. Nineteen patients (70%) with the preliminary diagnosis of malignancy of unknown etiology were admitted for surgery. In 23 patients (85%) the essential symptom was back pain, which preceded surgery by an average of 4 months. Thirteen patients (48%) were bedridden due to tumor spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Thus, surgical treatment (often combined with radiotherapy) appears particularly effective in restoring deficits and the ambulatory capacity in this setting. Of note, we also observed that totally bedridden patients have a poor survival, corroborating similar data by Rehak et al, 14 which obviously reflects the negative effect of reduced mobility and associated morbidity in the general condition of the patient.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, surgical treatment (often combined with radiotherapy) appears particularly effective in restoring deficits and the ambulatory capacity in this setting. Of note, we also observed that totally bedridden patients have a poor survival, corroborating similar data by Rehak et al, 14 which obviously reflects the negative effect of reduced mobility and associated morbidity in the general condition of the patient.…”
Section: Discussionsupporting
confidence: 92%
“…[9][10][11][12] However, the outcome of surgical treatment of patients with radiosensitive hematological malignancies is largely unknown, because they were mostly excluded from the aforementioned prospective studies and the only data are derived from small retrospective cohorts. 13,14 We retrospectively reviewed prospectively collected data of 50 consecutive patients surgically treated for MSCC due to lymphoma or myeloma between July 1993 and December 2012, and we documented the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of such treatment are not good, however: in patients who cannot move prior to surgery, only 38% report a significant improvement in their neurological status, while 62% of all patients report diminished mobility, notwithstanding decompression of the spinal cord [13].…”
Section: Discussionmentioning
confidence: 97%
“…However, there are studies showing that complications of radiotherapy are less than surgery (7,8,9). However, Rehak et al (10) suggested that the surgical approach for these tumors should be considered for long survival.…”
Section: Discussionmentioning
confidence: 99%